Syllabus Analysis of English for Hotel Receptionist Program with SKKNI in Kartu Prakerja by Mobile English - Raihaana Ziani Fahira; Neni Nurkhamidah (Lembaga Intelektual Muda Maluku, 2024)
Hotel receptionists who work as frontline in the hospitality industry are supposed to be able to perform their duties no matter where the guests come from. In handling foreigners, English can be used as a medium to communicate and serve guests. To achieve a certain level of communication in English; the employee could take training programs and courses to upskill their language level in ESP. This study intends to analyze a syllabus of the ESP. By conducting this study, the researcher tries to find out the competencies being taught in the program and the suitability of the SKKNI as the standard reference. The method used in this study was qualitative research with a content analysis approach. The subject of this study was a syllabus developed by Mobile English as a learning institution that partners with the Kartu Prakerja Program. The instrument used to examine the study was a form of table. The study's results examined only five competencies taught in the program out of 14 competencies that should be acquired based on the SKKNI. The finding implies that future improvements in the syllabus and the program are needed to help the student be competent in their role as hotel receptionists